The use of Janus Kinase inhibitors in hospitalized patients with COVID-19: Systematic review and meta-analysis - Indra Wijaya; Rizky Andhika; Ian Huang; Aga Purwiga; Kevin Yonatan Budiman; Muhammad Hasan Bashari; Lelani Reniarti; Rully Marsis Amirullah Roesli (Elsevier, 2021)
Background: The evidence of using JAK inhibitors among hospitalized patients with COVID-19 is conflicting. The systematic review and meta-analysis aimed to address the efficacy of Janus Kinase (JAK) Inhibitors in reducing risk of mortality among hospitalized patients with COVID-19. Methods: Several electronic databases, including PubMed, EuropePMC, and the Cochrane Central Register of Controlled Trials, with relevant keywords "COVID-19" AND ("JAK inhibitor" OR "Ruxolitinib" OR "Tofacitinib" OR "Fedratinib" OR "Baricitinib") AND ("Severe" OR "Mortality"), were used to perform a systematic literature search up to December 11, 2020. All studies pertinent to the predetermined eligibility criteria were included in the analysis. Our outcome of interest was all types of mortality, clinical improvement, and clinical deterioration. Dichotomous variables of our outcomes of interest were analyzed using Maentel-Haenszel formula to obtain odds ratios (ORs) and 95% confidence intervals (CI) with random-effects modeling regardless of heterogeneity. Results: Five studies with a total of 1190 patients and were included in this systematic review and meta-analysis. The use of JAK inhibitors was associated with a reduced risk of mortality (OR 0.51, 95% CI 0.28-0.93, P = 0.02; I2: 7.8%, P = 0.354) and clinical improvement (OR 1.76, 95% CI 1.05-2.95, P = 0.032; I2: 26.4%, P = 0.253). The use of JAK inhibitors was not associated with a reduced risk of clinical deterioration (OR 0.58, 95% CI 0.28-1.19, P = 0.136; I2: 24.1%, P = 0.267). Conclusion: The use of JAK inhibitors was significantly associated with a reduced risk of mortality, and clinical improvement in hospitalized patients with COVID-19.